EFFECT OF DIFFERENT CONCENTRATIONS OF HONEY ON SELECTED MICROORGANISMS - Ibegbulem, J. A.; Musa, S. K.; Idoko, S. S.; Baba, Dahiru; Abuh, H. A. (FUDMA Journal of Sciences, 2026)
This study investigated the antimicrobial properties of honey and the role of honey’s botanical origin on its antimicrobial efficacy at varying concentrations (12.5%, 25%, 50%, and 100%) against five pathogenic microorganisms: Escherichia coli, Bacillus cereus, Staphylococcus aureus, Salmonella typhi, and Pseudomonas aeruginosa. A ciprofloxacin control was used. Honey samples from Bauchi, Gombe, Plateau, and Kaduna States were tested via agar well diffusion. Results revealed significant (p
Keywords: Honey; Antimicrobial activity; Phytoecological profile; Zone of inhibition; Nigeria